Investigation of chaotic behavior and adaptive type-2 fuzzy controller approach for Permanent Magnet Synchronous Generator (PMSG) wind turbine system - Aceng Sambas; Ardashir Mohammadzadeh; Sundarapandian Vaidyanathan; Ahmad Faisal Mohamad Ayob; Amiral Aziz; Mohamad Afendee Mohamed; Ibrahim Mohammed Sulaiman; Mohamad Arif Awang Nawi (AIMS Mathematics, 2023)
This article begins with a dynamical analysis of the Permanent Magnet Synchronous Generator (PMSG) in a wind turbine system with quadratic nonlinearities. The dynamical behaviors of the PMSG are analyzed and examined using Poincare map, bifurcation model, and Lyapunov spectrum. Finally, an adaptive type-2 fuzzy controller is designed for different flow configurations of the PMSG. An analysis of the performance for the proposed approach is evaluated for effectiveness by simulating the PMSG. In addition, the proposed controller uses advantages of adaptive type-2 fuzzy controller in handling dynamic uncertainties to approximate unknown non-linear actions.